A method of vertical and horizontal force estimation by using air-filled material and camera for soft physical human-robot interaction: fundamental experiments. (3rd March 2016) - Lee, Suwoong; Kwon, Soono; Kim, Youngwoo; Lee, Kangwon
Abstract : A method of vertical and horizontal force estimation for soft physical human–robot interaction by using an air-filled material and a camera was proposed in this study. First, we considered hypotheses for vertical and horizontal force applied to the air-filled material. Second, the prototype of air-filled material and vision-based force-sensing device (AVFSD) was constructed. Based on the result of preliminary experiments, the relationships between force, pneumatic pressure, and contact surface displacement were formulated. The vertical and horizontal force could be estimated using the AVFSD with percentage errors of 3.6 and 5.8%, respectively, and the hypotheses were verified through the experiments. Graphical Abstract: